Immunosuppressive functions of melanoma cell-derived exosomes in plasma of melanoma patients - Whiteside, Theresa L. (Frontiers in Cell and Developmental Biology, 2023)
Tumor-derived exosomes (TEX) are a subset of small extracellular vesicles (sEV) present in all body fluids of patients with cancer. In plasma of patients with metastatic melanoma, numbers of exosomes produced by melanoma cells called MTEX are elevated. To study the role of MTEX in melanoma progression, immunoaffinity-based separation of MTEX from total plasma exosomes was performed. The surface of MTEX was decorated by various checkpoint inhibitory proteins, and upon coincubation with immune recipient cells, MTEX suppressed anti-tumor functions of these cells. MTEX emerge as a major mechanism of immune suppression in melanoma and thus might play a role in promoting melanoma progression.